Insects Associated with Kumat (Acacia senegal Willd) in the Arid Regions of Western Rajasthan - Parihar, D R; Singh, M P (Annals of Arid Zone, 2016)
The insect spectrum of Acacia senegal in the arid tracts encompassed 22 species of pestiferous insects, 15 species of flower visitors, 3 species of parasites and 7 species of predators (including 4 spider species). Important injurious insects were Ox)’carenus sp., Holotrichia sp., bruchids and Acameoderma aurifera. The flower visitors included Apis florea, Ha/ictus sp., Camponotus sp. and Xylocopa sp. The parasites were of Hymenopterious lineage, while the predators were of Acarine and Coleopterous origin.